2017
DOI: 10.1177/1010428317695921
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian target of rapamycin inhibitors, temsirolimus and torin 1, attenuate stemness-associated properties and expression of mesenchymal markers promoted by phorbol-myristate-acetate and oncostatin-M in glioblastoma cells

Abstract: The phosphatidylinositol 3-kinase/Akt/mammalian target of rapamycin signaling pathway is crucial for tumor survival, proliferation, and progression, making it an attractive target for therapeutic intervention. In glioblastoma, activated mammalian target of rapamycin promotes invasive phenotype and correlates with poor patient survival. A wide range of mammalian target of rapamycin inhibitors are currently being evaluated for cytotoxicity and anti-proliferative activity in various tumor types but are not explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Rapamycin also reduces GSCs sphere formation and the expression of GSCs-related markers, namely CD133 and Nestin [48]. This is in line with studies showing that targeting the PI3K/Akt/mTOR pathway represses stem-like cell properties in GBM cells by reducing the expression of other pluripotency-regulating transcription factors, such as NANOG and OCT-4 [116,117,118].…”
Section: Mtor Function In Glioblastoma Cancer Stem Cellsmentioning
confidence: 55%
See 1 more Smart Citation
“…Rapamycin also reduces GSCs sphere formation and the expression of GSCs-related markers, namely CD133 and Nestin [48]. This is in line with studies showing that targeting the PI3K/Akt/mTOR pathway represses stem-like cell properties in GBM cells by reducing the expression of other pluripotency-regulating transcription factors, such as NANOG and OCT-4 [116,117,118].…”
Section: Mtor Function In Glioblastoma Cancer Stem Cellsmentioning
confidence: 55%
“…In fact, hyper-activation of the Akt/mTOR pathway sustains GSCs migration and infiltration within the surrounding healthy brain parenchyma. As proof of concept, mTOR inhibitors suppress GSCs aggressiveness and invasive potential [117]. Moreover, mTOR inhibition downregulates both mRNA, protein levels, and the activity of the matrix metalloproteinases, MMP-9 and MMP-2, which promote tumor invasion through extracellular matrix degradation.…”
Section: Mtor Function In Glioblastoma Cancer Stem Cellsmentioning
confidence: 99%
“…The inhibition of mTOR by temsirolimus increases the cytotoxic and pro-apoptotic activity of PENAO (an inhibitor of adenine nucleotide translocase) on DIPG (diffuse intrinsic pontine gliomas) cells through the generation of reactive oxygen species, ATP depletion, and an increase in the activity of AMPK, with the subsequent inhibition of the PDGFRa /PI3K/mTOR and HSP90 signaling pathways [272]. Chandrika et al demonstrated that mTOR inhibitors like temsirolimus and torin significantly reduce the expression levels of mesenchymal markers (fibronectin, vimentin, and YKL40) and neural stem cell markers (Sox2, Oct4, nestin, and mushashi1) induced by the tumor promoter phorbol-myristate-acetate in LN-18 glioma cells, through the dephosphorylation of the transcriptional factor STAT3 [273]. In a phase II study, temsirolimus failed to exhibit antineoplastic effects in GBM patients, either as a monotherapy or combined with erlotinib.…”
Section: Introductionmentioning
confidence: 99%
“…Temsirolimus showed an antiproliferative effect on mouse low-grade glioma, GBM [396], and U87-MG glioma cells [397]. Temsirolimus modulates the NF-κB and PKC-α signaling pathways [398], inhibits the expression of mesenchymal markers, and repress stem-like cell properties in GBM cells [399]. Due to the limited activity of temsirolimus in glioma and GBM as a single agent, several trials have been conducted using multimodal therapies.…”
Section: Temsirolimusmentioning
confidence: 99%